Perlindungan Hukum Bagi Pekerja Atas Penetapan Upah Minimum yang Ditetapkan Oleh Gubernur yang Bertentangan dengan Peraturan Menteri Ketenagakerjaan Tentang Upah Minimum - Rahmi, Sri; Sinaga, Parbuntian; Setyowati, Retno Kus (Pusat Riset dan Inovasi Nasional, 2025)
Within the decentralization framework, the government sets the Regency/City Minimum Wage (UMK) as the wage standard. However, in 2021, the Governor of the Riau Islands Province established a UMK that did not comply with Ministry of Manpower regulations. This decision adversely affected workers, particularly members of labor unions, as well as the entire workforce in Batam City. The research addresses two key issues: first, the legal consequences of a regional head’s policy in determining the minimum wage; second, the form of legal protection for workers against a UMK that contradicts ministerial regulations. The study applies a normative juridical method. Findings indicate, under Article 82 of the Industrial Relations Dispute Settlement Act (UU PPHI), that a state administrative decision violating statutory provisions may be: (1) declared null (nietig/absolute nietig), (2) null and void by law (nietigheid van rechtswege), or (3) annulled (verniegbaar). The Tanjungpinang Administrative Court Decision No. 1/G/2021/PTUN.TPI declared that Governor’s Decree No. 1362 of 2020 on Batam UMK contained substantial defects and was annulled. Legal protection for workers is provided through dispute settlement procedures at the Administrative Court and/or administrative remedies as stipulated by applicable regulations.